Sudden deaths due to accidental leakage of Lindane from a storage tank in a village, Sitapur, Uttar Pradesh, India, 2020: A field epidemiological investigation. Issue 3 (8th June 2022) - Jain, Piyush; Kapoor, Amit; Rubeshkumar, Polani; Raju, Mohankumar; Joseph, Bency; Bhat, Prashant; Ganeshkumar, Parasuraman; Kesavachandran, Chandrasekharan Nair; Patel, Devendra Kumar; Manickam, Natesan; Kaur, Prabhdeep
Abstract : Background: Chemical leakages cause devastating health effects on humans. On 6 February 2020, seven deaths were reported following a hazardous chemical leakage in a village in Uttar Pradesh, India. We investigated the event to identify the cause and propose recommendations. Methods: We defined a case as sudden onset of breathlessness, headache, or death in the village, 6–7 February 2020. We conducted a house-to-house case search and calculated attack rate (AR) and case-fatality rate (CFR) by age and gender. We conducted an environmental investigation at the leakage site and sent the chemicals for forensic analysis. We obtained the cause of death through autopsy reports. Results: Out of 2, 942 residents, we identified 23 cases (AR = 8/1, 000) and seven deaths (CFR = 30%). The median age of the case was 42 years (range, 2–64 years). The AR was higher among males (14/1, 000 [19/1, 402]). All the 23 case-patients who were sleeping at the chemical leakage site or visited to witness the event developed symptoms, and all seven cases who were sleeping within 150 meters of the leakage site died. The environmental investigation revealed leakage of hazardous substances from the storage tank. Toxicology analysis confirmed the leaked chemical as Lindane (gamma-hexachlorocyclohexane), and autopsy reports confirmed the cause of death as asphyxia. Conclusions: Asphyxia following the leakage of Lindane from the storage tank possibly led to sudden deaths. We recommend using leak-proof tanks to ensure safe storage and disposal, law enforcement, and regulations to prevent people from staying close to chemical storage sites.